Inclusive leadership in relationship with psychological distress, organizational climate and social intelligence: a theoretical framework study - Ibnis Shaid Abdul Rajun; Soon Singh Bikar Singh; Zulfhikar Rabe (Secholian Publication, 2022)
The chain of global change phenomena occurring in life today has resulted in the urgent need to place world-class education as outlined in the Malaysia Blueprint 2013-2025. Hence, the Ministry of Education installed high-performing leaders in all schools by adopting the Transformative leadership style. The post-pandemic crisis is still haunting the lives of everyone, including teachers1 in schools. The urgency of change makes many teachers experience psychological distress. Therefore, the call to conduct research holistically in leadership, management, and resources to overcome the issue. Hence, this article describes a theoretical framework based on gaps and limitations in most past literature. The theoretical lens of social exchange theory contributes to the relationship between Inclusive Leadership, psychological stress, organizational climate and Social Intelligence. Eventually, the Inclusive Leadership style is not yet widely practiced in schools compared to the Transformational leadership style practiced since 2013. Based on literature reviews, this theoretical framework study uses to investigate Inclusive Leadership in curbing psychological distress among school teachers through organizational Climate and Social intelligence mediation. Therefore, the study of this theory aims to contribute to the field of Educational Leadership and Crisis management. And also beneficial not only to the Ministry of Education and to humankind.